Employer Stock and 401(k) Plans - Poterba, James M (American Economic Review, 2003)
The sharp decline in the stock prices of several firms at which employees held a large fraction of their 401(k) plan assets in company stock, including Enron, Global Crossing, Lucent, and Polaroid, has sparked a public-policy debate about investment options in 401(k) plans. At many large firms, particularly those with retirement saving plans that combine elements of an Employee Stock Ownership Plan (ESOP) with a traditional 401(k), a substantial fraction of defined-contribution retirement-plan assets are held in company stock. Such undiversified holdings are a source of concern because they raise the volatility of the retirement wealth for employees and expose some workers to the prospect of very small retirement values. Holding an undiversified position in employer stock may be particularly costly because of the potential correlation between company stock returns and the value of the worker’s human capital, which may depend on the company’s prospects. This paper reviews the extent of undiversified company-stock investments in 401(k) plans, evaluates the cost of such investments from an employee’s perspective, and discusses a range of policy actions that could address the excessive concentration of retirement plan assets.